Why do CEOs reciprocally sit on each other's boards? - Fich, Eliezer M.; White, Lawrence J. (Journal of Corporate Finance, 2005)
The reciprocal interlocking of chief executive officers is a non-trivial phenomenon: among large companies in 1991, about one company in seven was in a relationship whereby the CEO of one company sat on a second company's board and the second company's CEO sat on the first company's board. We develop hypotheses to distinguish whether this practice furthers the interests of shareholders or the private interests of the CEOs. Using a sample of large companies, we employ a probit model to test these hypotheses. Our empirical findings are that these reciprocal CEO interlocks primarily benefit the CEOs rather than their shareholders.